2022
DOI: 10.3389/fpsyt.2022.930059
|View full text |Cite
|
Sign up to set email alerts
|

Problematic substance use and its associated factors among street youth in Bahir Dar city, Ethiopia

Abstract: BackgroundProblematic substance use is becoming a common problem in marginalized groups such as street youths. However, there is a dearth of studies on the prevalence and factors associated with problematic substance use among street youth in Ethiopia.ObjectiveThe objective of this study was to determine the prevalence of problematic substance use and identify its associated factors among street youth.MethodsThis community-based cross-sectional study was conducted between June and July 2020. A total of 252 par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
3
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 36 publications
1
3
0
1
Order By: Relevance
“…This study revealed that there were a variety of factors including poverty, unemployment, family conflict and substance abuse that led the youth in the study to leave home for streets. This finding corroborates results of previous studies (Abebe, 2007;Demewozu, 2005;Shegaw et al, 2022). However, disability, alcoholic family, and displacement, which were commonly cited push factors in the previous studies, were not mentioned by this study participant as reasons for leaving home.…”
Section: Dscussionsupporting
confidence: 92%
See 1 more Smart Citation
“…This study revealed that there were a variety of factors including poverty, unemployment, family conflict and substance abuse that led the youth in the study to leave home for streets. This finding corroborates results of previous studies (Abebe, 2007;Demewozu, 2005;Shegaw et al, 2022). However, disability, alcoholic family, and displacement, which were commonly cited push factors in the previous studies, were not mentioned by this study participant as reasons for leaving home.…”
Section: Dscussionsupporting
confidence: 92%
“…While there may be a variety of reasons why a particular youth becomes homeless in urban areas, the research literature has identified some common factors. These include alcoholic families and parental conflict, poverty, unemployment, school violence, fast rising cost of living, high rates of population growth, rural-urban migration and displacement, disability, and inappropriate public policies (Abebe, 2008;Demewozu, 2005;Melese and Addis, 2020;Shegaw et al, 2022) and the search for a lost family pushed children and adolescents to the street whereas peer pressure or company of friends drew them there (Mathebula and Ross, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Mediante el presente trabajo de investigación y la revisión que fue llevada a cabo en base a los artículos seleccionados se pudo determinar según lo analizado esto sitúa al cannabis como la droga ilegal más consumida entre los jóvenes a nivel global y cuya prevalencia alta de consumo puede atribuirse a factores como la percepción de bajo riesgo, el fácil acceso y el bajo costo, así también se considera a los efectos de la misma más suaves en comparación a otras drogas psicodélicas; por otra parte el LSD también se perfila como una droga emergente y de importancia entre los jóvenes, sin embargo su prevalencia es mucho menor que la del cannabis sin embargo según la información analizada se considera que hay un repunte en el consumo de la misma (30,35).…”
Section: Discussionunclassified
“…The synthetic characteristics of Kush, akin to other emerging psychoactive substances, present profound risks to public health. The diversity and often unsupervised nature of these compounds' chemical structures contribute to unpredictable and severe health outcomes [4][5][6][7][8]. These outcomes are comparable to the detrimental effects of xylazine, colloquially termed the "Zombie" drug, which, when used in conjunction with fentanyl, has been associated with a troubling rise in overdose fatalities internationally [5,9,10].…”
Section: Introductionmentioning
confidence: 99%